Animal models of surgically manipulated flow velocities to study shear stress-induced atherosclerosis. Issue 1 (July 2015) - Winkel, Leah C.; Hoogendoorn, Ayla; Xing, Ruoyu; Wentzel, Jolanda J.; Van der Heiden, Kim
Abstract Atherosclerosis is a chronic inflammatory disease of the arterial tree that develops at predisposed sites, coinciding with locations that are exposed to low or oscillating shear stress. Manipulating flow velocity, and concomitantly shear stress, has proven adequate to promote endothelial activation and subsequent plaque formation in animals. In this article, we will give an overview of the animal models that have been designed to study the causal relationship between shear stress and atherosclerosis by surgically manipulating blood flow velocity profiles. These surgically manipulated models include arteriovenous fistulas, vascular grafts, arterial ligation, and perivascular devices. We review these models of manipulated blood flow velocity from an engineering and biological perspective, focusing on the shear stress profiles they induce and the vascular pathology that is observed.